A textual analysis of the African language expressions used during the #RhodesMustFall campaign. Issue 1 (23rd March 2018) - Motinyane, Mantoa
Abstract: The #RhodesMustFall is a student and staff movement that resulted in the removal of Rhodes' statue from the University of Cape Town in 2015. Language, in particular the #AfrikaansMustFall movement, took centre stage as one of the discourses that emerged following the removal of the statue. However, languages have received very little attention in research, despite the prominent role they played during this period. This paper therefore provides a textual analysis of rhetorical questions, metaphors and syntax of the phrases used on social media and in newspapers. through this analysis, we explore the relationship between the text, language form, and the context of the use of African languages during the campaign. We propose that, contrary to the commonly held belief, text-based communication coupled with social media innovations such as hashtags(#) played a major role in transferring feelings, emotions and states through specific language forms. We partly attribute the success at unity during this period to this creation of personal relationships, which were generated through a web of interconnected #communities with multiple identities. We further argue that within the #communities, group and individual identities were maintained in a manner that permeated the traditional relationships between language and ethnicity.